Pengaruh Edukasi Self-Management Hipertensi Terhadap Perilaku Self-Management Pada Pasien Hipertensi Di Puskesmas Desa Ciburayut - Nova Dwi Hardianti; Ritta Farma (Borneo Nursing Journal (BNJ), 2026)
Abstract Background: Dysmenorrhea is a common reproductive health problem experienced by adolescent girls and may interfere with their learning activities. Poor dietary patterns, particularly diets high in fat, low in fiber, and characterized by frequent consumption of fast food, have been reported to increase the risk of dysmenorrhea. A preliminary study conducted at SMA Negeri (State Senior High School) 1 Godean found that all seven respondents (100%) experienced dysmenorrhea, while four students (57.1%) reported skipping breakfast, reflecting poor dietary habits. Objective: To examine the relationship between dietary patterns and the incidence of dysmenorrhea among adolescent girls at SMA Negeri 1 Godean. Methods: This quantitative study employed a cross-sectional design. The study population consisted of 284 female students in 10th and 11th Grades at SMA Negeri 1 Godean. A total of 74 respondents were selected using purposive sampling based on the following inclusion criteria: aged 15–18 years, had experienced menarche, were willing to participate, were present during data collection, had an age at menarche of 12–14 years, had experienced menarche for 2–3 years, and had a normal body mass index (BMI). The exclusion criterion was incomplete questionnaire responses. Purposive sampling was applied to control for potential confounding variables, including BMI, age at menarche, and time since menarche. Dietary patterns were assessed using a 25-item Food Frequency Questionnaire (FFQ) based on food type and consumption frequency. The total score was divided by the number of items (25) to obtain the final score. Dietary patterns were categorized as poor (